Modelling of five-point bending beam test for asphalt surfacing system on orthotropic steel deck bridges. Issue 11 (19th September 2021) - Liu, Xueyan; Li, Jinlong; Tzimiris, Georgios; Scarpas, Tom
ABSTRACT: The orthotropic steel deck bridges (OSDBs) in the Netherlands consists mostly of multilayer system: top porous asphalt layer, guss asphalt layer, steel deck and two membrane layers. The five-point bending (5PB) beam test is the standard device in France for characterization of fatigue response of asphalt concrete surfacings used on orthotropic steel deck bridges. In this paper, an analytical solution for the 5PB beam test setup is presented first. In order to better understand the influence of geometrical, mechanical and structural parameters on the performance of the typical multilayer surfacing system of OSDBs, the 5PB test specimens with five structural layers have been investigated. The parametric study is performed at the numerical platform CAPA-3D that was developed at the Section of Structural Mechanics of TU Delft. The influences of the thickness of the asphalt layers and the mechanical properties of both top and bottom membrane layers are studied. The sensitivities of those influence factors are evaluated by the examination of the maximum tensile stress at the top surface of the porous asphalt layers and the strain distributions through the entire thickness of the specimen at two cross-sections.